2019
DOI: 10.3390/met9101065
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Evaluation of Biocompatibility and Implant Accuracy of the Electron Beam Melting and Commercial Reconstruction Plates

Abstract: The use of additive manufacturing in medical applications has become more prevalent over the last decade. Studies have proved that reconstruction plates with a mesh structure enhance the biocompatibility and bone-ingrowth formation. However, limited studies have been reported in the customization and in vivo clinical assessment of mesh implants. The purpose of this study was to investigate the surgical treatment and implant fitting accuracy using three different reconstruction plates. Fifteen goats were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Moiduddin et al obtained a titanium zygomatic implant with the EBM technique, using Ti-6Al-4V ELI (extra low interstitial) powder [144]. The same author [145] compared different kinds of Ti-6Al-4V ELI mandibular implants for goats: EBM plate with mesh, EBM titanium plate without mesh and a commercial reconstruction plate. They found that the reconstructed plates with mesh showed a better fit than the other ones.…”
Section: Maxillofacial Implantsmentioning
confidence: 99%
“…Moiduddin et al obtained a titanium zygomatic implant with the EBM technique, using Ti-6Al-4V ELI (extra low interstitial) powder [144]. The same author [145] compared different kinds of Ti-6Al-4V ELI mandibular implants for goats: EBM plate with mesh, EBM titanium plate without mesh and a commercial reconstruction plate. They found that the reconstructed plates with mesh showed a better fit than the other ones.…”
Section: Maxillofacial Implantsmentioning
confidence: 99%
“…Additive manufacturing (AM) provides an opportunity to fabricate a homogenous porous structure with controlled porosity and cell distribution. Several research studies have demonstrated the viability of additively manufactured scaffolds as a suitable solution for bone defects, thus maximizing the speed of recovery and bone repair [11,12]. Furthermore, additively manufactured customized scaffolds suit the individual anatomy and remain in place for longer periods, thus providing greater flexibility, higher stability, and good cosmetic results.…”
Section: Introductionmentioning
confidence: 99%
“…Electron beam melting (EBM) is one of the widely used metal 3D printing processes with a US Federal Drug Administration (FDA) approval [26]. It has been widely adopted by surgeons at an impressive rate and is used in a large variety of medical applications [27,28]. The 3D printed models can also be used for mock surgeries, pre-operative planning, surgical guides, and educational training purposes [29].…”
Section: Introductionmentioning
confidence: 99%